Delay-Dependent Dynamics of Switched Cohen-Grossberg Neural Networks with Mixed Delays. (12th May 2013) - Wang, Peng; Hu, Haijun; Jun, Zheng; Tan, Yanxiang; Liu, Li
Abstract : This paper aims at studying the problem of the dynamics of switched Cohen-Grossberg neural networks with mixed delays by using Lyapunov functional method, average dwell time (ADT) method, and linear matrix inequalities (LMIs) technique. Some conditions on the uniformly ultimate boundedness, the existence of an attractors, the globally exponential stability of the switched Cohen-Grossberg neural networks are developed. Our results extend and complement some earlier publications.